2009
DOI: 10.1159/000276765
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of the Tyrosine Phosphatase SHP-1 Defines a Subset of High-Grade Breast Tumors

Abstract: Objectives: Protein tyrosine phosphatases are key regulators of intracellular signaling that contribute to determining cancer cell growth, which thus makes them attractive targets for therapeutic and diagnostic agents. SHP-1 phosphotyrosine phosphatase is rarely expressed in epithelial tumor cells, but expression has been found in several breast cancer cell lines and tumors. To determine the potential significance of SHP-1 as a prognostic marker in the clinical setting, we examined SHP-1 protein expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…Insabato et al 27 reported that PTPN6 protein expression correlates with grade III in 7% of breast tumors. 27 This investigation has shown that PTPN6 overexpression was an independent predictor of poor 5, 10, and 15 years' disease-free survival in estrogen receptor-positive tumors with hazard ratios of 2.60 (P ¼ 0.029), 2.07 (P ¼ 0.069), and 2.13 (P ¼ 0.040), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Insabato et al 27 reported that PTPN6 protein expression correlates with grade III in 7% of breast tumors. 27 This investigation has shown that PTPN6 overexpression was an independent predictor of poor 5, 10, and 15 years' disease-free survival in estrogen receptor-positive tumors with hazard ratios of 2.60 (P ¼ 0.029), 2.07 (P ¼ 0.069), and 2.13 (P ¼ 0.040), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Insabato et al 27 reported that PTPN6 protein expression correlates with grade III in 7% of breast tumors. 27 This investigation has shown that PTPN6 overexpression was an independent predictor of poor 5, 10, and 15 years' disease-free survival in estrogen receptor-positive tumors with hazard ratios of 2.60 (P ¼ 0.029), 2.07 (P ¼ 0.069), and 2.13 (P ¼ 0.040), respectively. These findings together with results showing a correlation between high PTPN6 levels and grade III by Pearsons w 2 (correlation ¼ 0.153, P ¼ 0.013) and Spearman's rank (rank ¼ 0.151, P ¼ 0.015) support the findings of Insabato et al 27 This investigation has demonstrated that breast cancer tumors expressing NTRK1-pY674/pY675 together with low or undetectable levels of TP53 and PTPN6 are strongly associated with improved 5, 10, and 15 years' disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations